HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU TERHADAP KETEPATAN HASIL SERVIS ATAS BOLA VOLI PADA TIM PUTRA SMPN 10 TAPUNG KABUPATEN KAMPAR - Zulmaidar '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: the problem of the research was less ability on up service volley ball at male volley ball team of SMPN 10 Tapung. It is thought to because of less arm and shoulder muscle strenght when did up service, so that ball do not pass net or do not. The purpose of this research was to know about reletionship on power of arm nd and shoulder muscle with up service ability. Type of this research was correlation with aim to know extant reletionship between free variable and baound variable. After that, normality data test with Liliefors test with significant planed α = 0.05, and find the normality test of variable’s value was X, L0maks (0,114) < Ltable (0,242), normality test of variable Y, L0maks (0,147) < Ltable (0,242), with other word was normally of data distribution. Then continued to found r used product moment correlation analysis, if rresult > rtable so it was have significant reletionshio. The result of this research showed: it was significant connection between the power of arm and shoulder muscle when did up service, rresult(0,652) > rtable (0,602). So, Ho refused and Ha accepted. The conclusion was have significant reletionship between the power of arm and shoulder muscle over up service volleyball at male team of SMPN 10 Tapung Kampar Regency.Keywords: arm and shoulder muscle strenght, accuracy of volleyball up service.